The effect of solute segregation to deformation twin boundaries on the electrical resistivity of a single-phase superalloy. (September 2020) - Antonov, Stoichko; Li, Bernard; Gault, Baptiste; Tan, Qing
Abstract: It is critical to control the electrical resistivity of alloys used for wires in harsh environment, e.g. for implanter bio-devices. As-drawn and aged MP35N wires were investigated, exhibiting increasing resistivity with aging time and temperature, in contrast to precipitate-forming alloys. We reveal Cr segregation to deformation twin boundaries upon aging, which effectively facilitates electron scattering and increases the resistivity. Since the diffusion of Cr atoms to these fault planes is rather fast, the larger increment of resistivity occurs very quickly, especially at elevated temperatures. This mechanism is likely active in a wide range of non-dilute alloys that form extended fault planes. Graphical abstract: Image, graphical abstract